Pricing Risk-Adjusted Deposit Insurance: An Option-Based Model - Ronn, Ehud I.; Verma, Avinash K. (Journal of Finance, 1986)
This paper presents a methodology for arriving at empirical estimates of deposit insurance premiums from market data by using isomorphic relationships between equity and a call option, and insurance and a put option. The data utilizes the market value of equity to solve for the asset value and its volatility. Market perceptions of FDIC bailout policies are explicitly modeled so as to eliminate the bias in inverted values of assets and their volatility. Sensitivity analyses are performed to show that rank orderings based on premiums are robust to changes in specification, thus facilitating allocation of aggregate premium across banks.